Single machine scheduling for multi-assembly jobs with preemption - L. Boonma (2018)
© 2016 IEEE. This research proposes a mathematic model for scheduling multi-assembly jobs with uncertain arrival of raw materials or sub-assembly parts and allowable preemption, aiming to minimize tardiness penalty and set-up cost under a single machine. The experimental results show that using the exact algorithm (Branch and Bound) in Lingo 12 is not capable of solve the large-sized problems. Balancing tardiness and set-up cost (BTS) algorithm, therefore, is developed and is capable to solve much larger size of the problem with reasonable solution quality and computational time.